Vozes da Militância Nova Iguaçu nas décadas de 1970 e 1980 - Kronemberger, Adriana Bastos (2023)
This thesis, developed at the Pontifical Catholic University of São Paulo, under the guidance of Professor Luiz Antonio Dias, addressed the urban social movements of the 1970s and 1980s, focusing on narratives of struggle and social transformation in Nova Iguaçu. It aimed to interview social activists who worked in that city in the aforementioned decades. These people fought for the most basic social rights of the local population, for Human Rights in a broader sense and against the civil-military dictatorship that was installed in Brazil after the 1964 coup and remained until 1985. It was intended, through the interviews produced, examine the representations that these people develop about their struggles, their participation, conquests, losses, and organizations in the urban social movements of the referred decades. Thus, observing the particularities of the struggles of the people of the city. Aiming to show that there was resistance to the civil-military dictatorship in Nova Iguaçu, but there is also the difficulty of quantifying the violence in the city.Therefore, the hypothesis of this work would be to present the daily struggles through the preservation of memory. In the development of the interviews, the methodology of oral History was used. The interviewees were chosen through indication and self-offering to provide testimonials about their participation in the social struggles of Nova Iguaçu, together with the then bishop of that city, Dom Adriano Hypólito who, inspired by Liberation Theology, became a person of recognized participation in the fight for human rights in Brazil, during the “years of lead”. Based on the testimonies provided, an analysis was made using them, as well as a comparison with reports from the time and official documents, respecting existing studies on memory and representation. The justification for analyzing these reports is to deepen the studies on the urban social movements of the 1970s and 1980s and to recognize in such movements, seeds of continuity of those struggles that can be cultivated more and more for the continuation of the conquests of the most basic social rights, that still do not reach the entire population, on the contrary, the social chasms have only increased